The effectiveness of a "EspaiJove.net"- a school-based intervention programme in increasing mental health knowledge, help seeking and reducing stigma attitudes in the adolescent population: a cluster randomised controlled trial - Rocío Casañas; Pere Castellvi; Juan-José Gil; María Torres-Torres; Jesica Barón; Mercè Teixidó; Hernán María Sampietro; Marta Díez; Raúl Fernández; Raquel Sorli; Patricia Siñol; Francisca Jurado; et al. (BMC, 2022)
Abstract Background The aim of this study is to evaluate the short- and long-term effects of the universal mental health literacy intervention "EspaiJove.net" in increasing mental health knowledge, help seeking and reducing stigma attitudes in the adolescent population. We also examine whether these effects depend on the intervention intensity.  Methods A clustered school-based randomised controlled trial (cRCT) design. Subjects: 1,298 secondary pupils aged 13 and 14 were recruited from 18 schools in Barcelona (Spain) between September 2016 and January 2018. Intervention: Three programmes were assessed: 1) Sensitivity Programme (SP; 1 h); 2) Mental Health Literacy (MHL; 6 h); 3) MHL plus a first-person Stigma Reduction Programme (MHL + SR; 7 h); 4) Control group (CG): waiting list. Outcome measures: 1) MHL: EspaiJove.net EMHL Test (First part and Second Part); 2) Stigma: RIBS and CAMI; 3) Help-seeking and use of treatment: GHSQ. Analysis: The data was collected at baseline, post-intervention and 6 and 12 months later. An intention-to-treat analysis and imputation method was used to analyse the missing data. Intervention effects were analysed using multilevel modelling. Results One thousand thirty-two students were included (SP = 225; MHL = 261; MHL + SR = 295 and CG = 251). The MHL and MHL + SR interventions showed short- and long-term an increase in knowledge compared to SP and CG, but no significant change post-intervention or over time (First part p = 0.52 and Second part p = 0.62) between intervention groups and CG. No significant changes were found in stigma scores post-intervention or over time (CAMI p = 0.61 and RIBS p = 0.98) or in help-seeking scores (parent p = 0.69; teacher p = 0.23 and healthcare professional p = 0.75). The MHL + SR intervention was the best valued and recommended (p < 0.005). Conclusions The three interventions of the EspaiJove.net programme (SP, MHL and MHL + SR) seem not to be effective in terms MHL, Stigma and help-seeking behaviours. The contact with a person who has experimented mental illness first-hand did not reduce stigma attitudes. Further research should deal with the heterogeneity of MHL interventions (concept, duration and measures) and identify which components of stigma interventions are effective. Trial registration ClinicalTrials.gov identifier: NCT03215654 (registration date 12 July 2017).